Fostering self-regulated entrepreneurial learning in entrepreneurship education - Fahrbach, Manuel; Jenert, Tobias; Fust, Alexander; Bellwald, Noah; Winkler, Christoph (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Self-Regulated Learning; Entrepreneurship Education; Entrepreneurship Research

Transferability as a key to impactful entrepreneurship education outcomes: a new quest - Winkler, Christoph; Jenert, Tobias; Fust, Alexander (Annals of Entrepreneurship Education and Pedagogy - 2025)
Keywords: Methodology; Entrepreneurship Education; Entrepreneurship Research

The Multifaceted Nature of Self-Regulation in Entrepreneurship: A Latent Class Analysis - Jenert, Tobias; Büker, Ronja (21th Biennial EARLI Conference)

Education through Entrepreneurship: Developing self-direct competencies in Higher Education - Jenert, Tobias; Büker, Ronja (EARLI SIG 4 & 17 Conference 2024)

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Designing Self-Regulation interventions for different target groups in Entrepreneurship Education - Jenert, Tobias; Büker, Ronja (20th Biennial EARLI Conference)

Mit dem SREL-Training unternehmerische Selbstkompetenzen entwickeln - Büker, Ronja; Jenert, Tobias; Fust, Alexander Paul; Fahrbach, Manuel; Bellwald, Noah; Winkler, Christoph (Erziehung & Unterricht)

Unternehmer*innen und Selbstregulation - ein Widerspruch? - Büker, Ronja; Jenert, Tobias (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

From entrepreneurial experience to expertise: A self-regulated learning perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Journal of Small Business Management)
Entrepreneurial experience alone may not necessarily guarantee venture success. Some entrepreneurs develop into experts through learning from their experiences, whereas others fail to do so. To explain the missing link between experience and expertise, we introduce a social-cognitive model of self-regulated entrepreneurial learning (SREL) to demonstrate how entrepreneurial expertise can be systematically developed to increase the probability of entrepreneurial success. We identify key self-regulatory learning processes essential to entrepreneurial learning by developing propositions and related practice-oriented applications of the SREL model for entrepreneurs.